3-Functionalised benzenesulphonamide based 1, 3, 4-oxadiazoles as selective carbonic anhydrase XIII inhibitors: Design, synthesis and biological evaluation. (1st April 2021) - Swain, Baijayantimala; Abhay,; Singh, Priti; Angeli, Andrea; Aashritha, Kamtam; Nagesh, Narayana; Supuran, Claudiu T.; Arifuddin, Mohammed
Graphical abstract: A new series of benzenesulphonamide linked-1, 3, 4-oxadiazole hybrids (6a –s ) has been synthesized and tested for their carbonic anhydrase inhibition against CA isoforms hCA I, II, IX, XIII. Most of the molecules exhibited amusing inhibition constant in nanomolar range while some are being more active than the standard drug acetazolamide (AAZ) on hCA XIII. Out of 19 molecules tested, compound 6e (75.8 nM) was found 3 times more potent than AAZ (250.0 nM) against hCA I isoform and compound 6e (15.4 nM), 6g (16.2 nM), 6h (16.4 nM), 6i (17.0 nM) were found to be more potent than AAZ (17.0 nM) against hCA XIII isoform. Abstract: A new series of benzenesulphonamide linked-1, 3, 4-oxadiazole hybrids (6a –s ) has been synthesized and tested for their carbonic anhydrase inhibition against human (h) carbonic anhydrase (CA) isoforms hCA I, II, IX, and XIII. Fluorescence properties of some of the synthesized molecules were studied. Most of the molecules exhibited significant inhibitory power, comparable or better than the standard drug acetazolamide (AAZ) on hCA XIII. Out of 19 tested molecules, compound 6e (75.8 nM) was 3 times more potent than AAZ (250.0 nM) against hCA I, whereas compound 6e (15.4 nM), 6g (16.2 nM), 6h (16.4 nM) and 6i (17.0 nM) were found to be more potent than AAZ (17.0 nM) against isoform hCA XIII. It is anticipated that these compounds could be taken as the potential leads for the development of selective hCA XIII isoform inhibitors with improved potency.